1966
DOI: 10.1103/physrev.148.715
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Optical Properties of High-Resistivity Gallium Phosphide

Abstract: Static and dynamic photoconductive properties of single-crystal high-resistivity (compensated) GaP have been studied in the intrinsic and near infrared spectral region at 300°, 77°, and 27°K. Room-temperature resistivities in excess of 10 14 12-cm have been produced by copper diffusions into either n-or />-type GaP. Large photoconductivity gains have been measured for intrinsic radiation: Gains in some cases exceeded 10 4 for fields of 10 3 V/cm. The photoconductivity is strongly influenced by traps. In />-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1968
1968
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 11 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…The Ohmic activation energy we describe (^0.7 eV) has been reported by other authors 13,14 and has been attributed to the presence of a Cu impurity at this energy distance from the valence band. We have shown however that a correct interpretation yields an energy level located about 1 eV from the valence band.…”
Section: B Gallium Phosphidementioning
confidence: 76%
See 1 more Smart Citation
“…The Ohmic activation energy we describe (^0.7 eV) has been reported by other authors 13,14 and has been attributed to the presence of a Cu impurity at this energy distance from the valence band. We have shown however that a correct interpretation yields an energy level located about 1 eV from the valence band.…”
Section: B Gallium Phosphidementioning
confidence: 76%
“…(1) and (2) with Eqs. (13) and (14) [or (15) and (16) N q and (/xoN c ). Of course, if the intrinsic quantity JJLON C were known from independent information, then measurement of Vm would simply provide a self-consistency check.…”
Section: G G Roberts and F W Schmidlinmentioning
confidence: 99%
“…7 for an unpolished sample. Equation (2) has been used to calculate the absolute change in absorption coefficient : see Fig. 11 right hand side axis.…”
Section: +I-mentioning
confidence: 99%
“…In GaP:Cu [7] it was found that both initially n-type and p-type GaP greatly increased in resistivity, but the concentration of deep donors was orders of magnitude below what would be required to explain this change by compensation mechanisms. Recently, it has been observed that Li doped GaAs [8] attains resistivities in the 10 7 Ω cm range regardless of the type before diffusion.…”
mentioning
confidence: 96%